Pathogenic bacteria and TNF do not induce production of macrophage migration inhibitory factor (MIF) by human monocytes - Temple, S.; Cheong, K.; Price, Patricia; Waterer, G. (Academic Press, 2009)
Elevated serum macrophage migration inhibitory factor (MIF) is associated with severe sepsis, but it is not clear whether bacteria stimulate synthesis of MIF by blood leukocytes directly or via induction of TNF. Here we assess production of MIF mRNA and protein by blood leukocytes from healthy human subjects (n = 28) following exposure to bacteria commonly associated with sepsis (Escherichia coli and Streptococcus pneumoniae). Bacteria did not increase levels of MIF mRNA or secreted protein. CD14 + monocytes were the main cell type producing MIF before and after stimulation. Exposure of leukocytes to TNF did not induce MIF. Hence elevated levels of serum MIF observed in sepsis may not reflect MIF produced by blood leukocytes stimulated directly by bacteria or TNF.